Roles of the Metabolic Syndrome, HDL Cholesterol, and Coronary Atherosclerosis in Subclinical Inflammation - Rein, Philipp (American Diabetes Association, 2010)
OBJECTIVE: The metabolic syndrome (MetS) and coronary artery disease (CAD) frequently coincide; their individual contribution to inflammation is unknown. RESEARCH DESIGN AND METHODS: We enrolled 1,010 patients undergoing coronary angiography. Coronary stenoses ≥50% were considered significant. The MetS was defined according to American Heart Association–revised National Cholesterol Education Program Adult Treatment Panel III criteria. RESULTS: C-reactive protein (CRP) did not differ between patients with significant CAD and subjects without significant CAD (P = 0.706) but was significantly higher in MetS patients than in those without MetS (P < 0.001). The MetS criteria low HDL cholesterol (P < 0.001), large waist (P < 0.001), high glucose (P < 0.001), and high blood pressure (P = 0.016), but not high triglycerides (P = 0.352), proved associated with CRP. When all MetS traits were considered simultaneously, only low HDL cholesterol proved independently associated with CRP (F = 44.19; P < 0.001). CONCLUSIONS: CRP is strongly associated with the MetS but not with coronary atherosclerosis. The association of the MetS with subclinical inflammation is driven by the low HDL cholesterol feature.